2022
DOI: 10.1371/journal.pone.0275005
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle environmental sustainability and cumulative energy assessment of biomass pellets biofuel derived from agroforest residues

Abstract: This study was carried out to produce low-emitting biomass pellets biofuel from selected forest trees such as (Cedrus deodara and Pinus wallichiana) and agricultural crop residues such as (Zea mays and Triticum aestivum) in Gilgit-Baltistan, Pakistan using indigenously developed technology called pelletizer machine. Characterization, environmental life cycle impact assessment, and cumulative energy demand of biomass pellets biofuel produced from selected agriculture crops and forest tree residues were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Studies in Thailand [ 188 ] Canada [ 198 ] and China [ 199 ] have also reported significant environmental pollution due to pellets production. A lifecycle assessment of wood pellets from agro-forest species in Pakistan reported that the intense fossil fuel consumption associated with fuel production was the largest contributory factor to significant environmental impacts; acidification (0.006 kg SO2 eq/kg pellets), abiotic depletion (0.018 kg Sb eq/kg pellets), marine aquatic ecotoxicity (417.803 kg 1,4-DB eq/kg pellets), human toxicity (1.107 kg 1,4-DB eq/kg pellets), freshwater aquatic ecotoxicity (0.191 kg 1,4-DB eq/kg pellets), eutrophication (0.001 kg PO4 eq/kg pellets), global warming (0.802 kg CO2 eq/kg pellets), and terrestrial ecotoxicity (0.008 kg 1,4-DB eq/kg pellets) [ 200 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies in Thailand [ 188 ] Canada [ 198 ] and China [ 199 ] have also reported significant environmental pollution due to pellets production. A lifecycle assessment of wood pellets from agro-forest species in Pakistan reported that the intense fossil fuel consumption associated with fuel production was the largest contributory factor to significant environmental impacts; acidification (0.006 kg SO2 eq/kg pellets), abiotic depletion (0.018 kg Sb eq/kg pellets), marine aquatic ecotoxicity (417.803 kg 1,4-DB eq/kg pellets), human toxicity (1.107 kg 1,4-DB eq/kg pellets), freshwater aquatic ecotoxicity (0.191 kg 1,4-DB eq/kg pellets), eutrophication (0.001 kg PO4 eq/kg pellets), global warming (0.802 kg CO2 eq/kg pellets), and terrestrial ecotoxicity (0.008 kg 1,4-DB eq/kg pellets) [ 200 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moisture content and ash content of biomass pellets produced from different selected species.The highest heating value among all nine species was for Melia azedarach wood pellets(24.79 MJ/kg), followed by Softwood mix and Pinus wallichiana biomass pellets with 23.84 and 23.39 MJ/kg, respectively. The HHV suggested by the Italian standard CTI-R04/05 is ≥16.91 MJ/kg[37]. The low heating values among all eight species were recorded lowest (20.24 MJ/kg) in Abies pindrow, followed by Parthenium hysterophorus and Albizia lebbeck with values of 20.26 and 20.80 MJ/kg as documented in Table4.…”
mentioning
confidence: 84%
“…The moisture % was calculated using a laboratory electric oven and precision balance on a standard of (ASTM.D1762) [37]. A moisture tester is also used to determine the moisture content.…”
Section: Samples Characterization 271 Determination Of Moisture Perce...mentioning
confidence: 99%
See 1 more Smart Citation
“…New design ideas, new materials, and optimised power delivery with a limited right of way will be needed for future power transmission lines [ 101 ]. Lightweight materials that address efficiency and environmental concerns drive power transmission businesses such as those that manufacture cross arms [ 102 , 103 , 104 ]. FRP composites can replace conventional materials and offer essential applications for a more sustainable society [ 105 , 106 , 107 , 108 ].…”
Section: Future Development Of Cross Arm Structures In Latticed Trans...mentioning
confidence: 99%